Measuring workload for tuberculosis service provision at primary care level: a methodology - Blok Lucie; van den Hof Susan; Mfinanga Sayoki G; Kahwa Amos; Ngadaya Esther; Oey Liesbeth; Dieleman Marjolein (BMC, 2012)
Abstract We developed and piloted a methodology to establish TB related work load at primary care level for clinical and laboratory staff. Workload is influenced by activities to be implemented, time to perform them, their frequency and patient load. Of particular importance is the patient pathway for diagnosis and treatment and the frequency of clinic visits. Using observation with checklists, clocking, interviews and review of registers, allows assessing the contribution of different factors on the workload.